Primsiz sosyal güvenlik sisteminde belediyelerin yeri ve İstanbul Büyükşehir Belediyesi uygulamaları - Kılıç, Sami (My University, 2001)
Bu çalışmanın amacı Türkiye'de primsiz sosyal güvenlik sistemi içinde belediyelerin yeri gelişmiş ülkelerdeki yerel yönetim uygulamalarından daha yetersiz olduğunu gösterme çabasını taşımaktadır. Bu mukayesenin temelinde ise ülke yönetiminde demokratik yerinden yönetimin gelişmesi ve ekonomik kalkınma düzeyi bulunmaktadır. Sosyal Güvenlik literatüründe yeralan kaynaklar başta olmak üzere sosyal güvenlik içinde primsiz kısmın gelişimini sergilemeye çalıştım. Belediyelerle ilgili kısımda Türkiye'deki belediyelerin yapısını ve gelişimini temel eserlerden özetlerken, mali durumlarını Devlet Planlama teşkilatı ve Devlet İstatistik Enstitüsü web sitelerinden rakamlarla ifade ettik. İstanbul Büyükşehir Belediyesi örneğini birincil kaynaklardan belirterek açıkladık. Özellikle deprem kriz raporunda koordinasyon içerisinde yardım sandığı saymanı olmam sebebiyle çalışmalar içerisinde bizzat bulunarak yapılmış olan faaliyetler ayrıntılı bir şekilde ortaya konmuştur. Bu çalışma sonucunda yerel yönetimler için öncelikle Cumhuriyetin ilk yıllarında M. Kemal Atatürk 'ün hazırlattığı Belediye Kanununa aykırı diğer yasal unsurların kaldırılması ve yerel yönetimler reformunun yapılması, gerektiği bulgusuna ulaşılmıştır. Türkiye'nin yaşamış olduğu ekonomik kriz nedeniyle ülke nüfusunun 1/ 5 'inin yaşadığı ve ekonomik faaliyetlerin ise %40'ının gerçekleştiği İstanbul'da yaşamı sürdürmenin zorlaşması nedeniyle insanların sosyal yardımlara duyduğu ihtiyacın artmasına rağmen karşılanamayan bu talep bir sorun halini almaktadır. Primsiz sosyal güvenliğin unsuru olan belediyelerin yapacağı faaliyetlerle bu sorunun çözümünde en etkili kurumlar olması gerekmektedir. Dünyada Japonya, Amerika, Kara Avrupası, İngiltere vb. ülkeler sosyal yardımla iligili yetkileri ve kaynakları yerel yönetimlere devretmişlerdir. Ayrıca Dünya Bankası 1999-2000 raporlarında şehirler dünyada ekonomik kalkınmanın itici gücü olarak görülmektedir. İstanbul kenti ve yerel yönetimi sahip olduğu potansiyelle sosyal yardım konusunda daha etkin ve verimli olması yönündeki engellerin kaldırılması gerekmektedir.

The target of this study is to point out the insufficient situation of the implementation in Turkish Municipalities with their unpaid premium system of the social security comparing in the developed countries. The main parts of this comparison for this study has been set on the basis of the level of economical development and decentralized democratic Administration . Apart from the sources of ordinary species at the Social Security Literature I have tried here to present the progression story of the unpaid premium version of the mentioned system. The municipal side of the study for the whole Public Administration in Turkey has been contributed for a summarize by the very best known public sources in Turkey and their fiscal status has been granted and checked by the formal figures stated official websites of (DPT) The State Planning Organization and (DİE) The State Statistical Institute. As to The Metropolitan Municipality of Istanbul the information has been achieved at the first hand in each detail. Especially for the period of the Turkish Earthquake while I was assigned the only liable and authorized Accountant Supervisor of the Relief Organization of the Crisis performing personally I have stated in my this study all the activities with their actual figures and fine details. In this preparation repeatedly there has been reached to the point of the cancellation of some discordant Acts in the whole Municipal Law enacted once by Mustafa Kemal ATATÜRK The Leader of Modern Turkish Republic beside doing the adaptation of necessary reforms at the total board of the current law of The Local Administration. Although a great need to social aids for the people of İstanbul where the %40 of the total incomes have been collected and other finance activities occurred and 1/ 5 of the total population have been living the social relieves on account of the current crisis have been becoming a great and the serious matter which haven't been afforded still. The Municipalities which are the main parts of the system of the Turkish version of unpaid premiums ought to be considered the most effective public Administrative in Turkey. In this view Japan, USA, European Countries, Britain etc.. which are called the developed countries on the world have turned over all their liabilities, competence and authorization to the Local Administrative already. This my opinion has been proved by the reports of The World Bank 1999-2000 that the City-Local Administration are considered the most driving forces in the global World. As a very compact result of this study on the progressive way to development of Istanbul the world Metropolitan City with it's Local Management and other potentials there ought to be removed jurisprudent obstacles on the Social Aids and relating activities.
Keywords: Belediyeler-istanbul; Devletin finanse ettiği sigorta; Sigorta; Sigortacılık; Sosyal Güvenlik-sigorta